RELIGIOUS POLICY IN THE COVID-19 PANDEMIC AND THE PROPHET’S HADIS - Fatichatus Sa'diyah (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2023)
This article discusses the arguments of the Prophet’s hadis which are textually contrary to government policies, especially during the covid-19 pandemic. Since the outbreak of covid-19 in early 2020, the government has provided many religious policies for Muslims that have had a lot of impact on their religious behavior. Among them are getting used to praying at home because many mosques are closed, getting used to praying dhuhur on Friday because Friday prayers are abolished, not shaking hands because it will cause physical contact with each other, not attending to pay respects to Muslim brothers who died. While all these behaviors are contrary to the textual meaning of the Prophet’s hadis. For example, regarding the threat who leave Friday prayers, the virtue of praying in congregation at the mosque, the virtue of shaking hands when meeting each other, the virtue of carrying out joint obligations in the form of final respect for Muslim brothers who died. Judging by using the theory of structural functionalism popularized by Robert K Merton, it is explained that the basic assumption is that every structure in a social system is functional with respect to the other parts Therefore, this article concludes that between the two realities –religious policies during a pandemic and religious narratives in hadis– do not cause conflict, in fact there is a relationship between one and the other. This is even more so if the traditions are understood using a contextual approach.